Synthetic and Natural Polycationic Polymer Nanoparticles Interact Selectively with Fluid-Phase Domains of DMPC Lipid Bilayers - Mecke, Almut (2005)
Polycationic polymers are known to disrupt lipid bilayers. In this letter, we report the dependence of this disruption on the lipid structural phase. DMPC bilayers are exposed to two polycationic polymeric nanoparticles, PAMAM dendrimers and MSI-78. We find that regions of the bilayer that are in the gel phase are unaffected by the presence of polymers, whereas the liquid phase is disrupted.